Bioinformatic analysis of the protein/DNA interface - Schneider, Bohdan; Cerný, Jirí; Svozil, Daniel; Cech, Petr; Gelly, Jean-Christophe; de Brevern, Alexandre G (Nucleic acids research, 2014)
To investigate the principles driving recognition between proteins and DNA, we analyzed more than thousand crystal structures of protein/DNA complexes. We classified protein and DNA conformations by structural alphabets, protein blocks [de Brevern, Etchebest and Hazout (2000) (Bayesian probabilistic approach for predicting backbone structures in terms of protein blocks. Prots. Struct. Funct. Genet., 41:271-287)] and dinucleotide conformers [Svozil, Kalina, Omelka and Schneider (2008) (DNA conformations and their sequence preferences. Nucleic Acids Res., 36:3690-3706)], respectively. Assembling the mutually interacting protein blocks and dinucleotide conformers into 'interaction matrices' revealed their correlations and conformer preferences at the interface relative to their occurrence outside the interface. The analyzed data demonstrated important differences between complexes of various types of proteins such as transcription factors and nucleases, distinct interaction patterns for the DNA minor groove relative to the major groove and phosphate and importance of water-mediated contacts. Water molecules mediate proportionally the largest number of contacts in the minor groove and form the largest proportion of contacts in complexes of transcription factors. The generally known induction of A-DNA forms by complexation was more accurately attributed to A-like and intermediate A/B conformers rare in naked DNA molecules.
Keywords: DNA vazebné proteiny; vazba proteinů; DNA; Nucleic Acid Conformation; konformace nukleové kyseliny; voda; Models, Molecular; Computational Biology; Phosphates; Data Interpretation, Statistical; Water; Protein Conformation; molekulární modely; interpretace statistických dat; DNA-Binding Proteins; konformace proteinů; výpočetní biologie; fosfáty; Protein Binding